Ondansetron reducing pain on injection of etomidate: a controlled randomized study - Azimaraghi,Omid (2014)
Introduction: Etomidate causes pain when injected intravenously. In this study we sought to determine if pretreatment by ondansetron reduces the pain on injection of etomidate. Methods: In this randomized, double blinded, placebo-controlled clinical trial, 20 patients of both sexes aged between 18 and 50 years of American Society of Anesthesiologists (ASA) physical status class I or II, whom were candidates for various elective surgical procedures and need more than one intravenous access were enrolled in the study. On arrival to the operating room two 22 gauge cannulas were inserted into veins on the dorsum of both hands. Following the infusion of 100 mL normal saline into both intravenous lines, using an elastic band, venous drainage of hands was occluded at midarm. The patients were administered 8 mg (2 mL) of ondansetron into one hand and 2 mL of 0.9% saline into the other hand at the same time. The elastic band was removed after 1 min and 2 mg (1 mL) of etomidate was administered at the same rate simultaneously into intravenous lines. The patients were asked to give a score of pain based on a verbal analog scale (VAS) to each hand. Results: A total number of 20 patients were studied (male = 55%, female = 45%). The mean age of the participants was 37.5 ± 13.1 years old and the mean weight was 67.7 ± 7.3 kg. The mean VAS for injection pain of etomidate after pre-administration of intravenous ondansetron was 1.5 ± 1.2 which was lower compared to pre-administration of placebo (3.2 ± 2.8, p < 0.05). Conclusion: This study illustrates that pre-treatment with intravenous ondansetron significantly reduces the pain on injection of etomidate.